"Auditoría y su relación don el desarrollo del gobierno autónomo descentralizado de la parroquia rural de Patricia Pilar cantón Buena Fe, año 2012" - Sarche Mier, Yojana Isabel (2015)
Financial Audit is directed to issue an opinion on the economic processes of the entity and also the analysis of the reasonableness of the financial statements in order to provide recommendations to improve the efficiency of their operations. This research was conducted in the Autónomous Government Decentralized Rural parish of Patricia Pilar, belonging to the canton Buena Fe Los Rios province. Which persecute meet the following objective: "To determine the relationship of the financial audit with the development of the Autónomous Government Decentralized Rural Patricia Pilar Parish Canton Good Faith, the year 2012". Through the process different research techniques were used: as the interview obtained with Mr. Treasurer of the entity to gain a broad understanding of the activities and history of the institution, implementation of internal control questionnaire in the accounting department and method Analytical whereby the information obtained during the test was analyzed, the same that allowed us to achieve results that were obtained from the analysis of financial statements and documentation that support one of the most important was that the fixed assets are not I applied them any depreciation method reflects the same purchasing power in years ago in the statement of financial position, therefore it is recommended to fully implement the rules of government internal control and other legal provisions in order to obtain adequate development activities and good decision making.